2022
DOI: 10.1111/all.15529
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing of single allergen‐specific memory B cells after grass pollen immunotherapy: Two unique cell fates and CD29 as a biomarker for treatment effect

Abstract: Background Sublingual immunotherapy (SLIT) for grass pollen allergy can modify the natural history of allergic rhinitis and is associated with increased allergen‐specific IgG4. IgG4 competitively inhibits functional IgE on the surface of effector cells, such as mast cells and basophils, from binding to allergens. To further understand the important role memory B‐cell (Bmem) responses play in mediating the beneficial effects of SLIT, we assessed changes in allergen‐specific Bmem subsets induced by SLIT for gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Yao et al [ 122 ] demonstrated that CD23 expression on switched memory B cells, positively correlated with disease severity and clinical efficacy of HDM-SCIT in patients with AR, and also correlated with improvement of the symptom scores. Consistently, grass pollen SLIT induces Lol p 1-specific memory B cells with upregulated expression of surface IgG4, CD23, and CD29 [ 123 ]. The serum C-X-C motif ligand 13(CXCL13) but not B cell-activating factor after HDM-SCIT in pediatric AR have clinical values for biomarkers, being CXCL13 level higher in effective AIT group [ 124 ].…”
Section: Predictive Biomarkers For Ait Outcomes In Allergic Diseasesmentioning
confidence: 93%
“…Yao et al [ 122 ] demonstrated that CD23 expression on switched memory B cells, positively correlated with disease severity and clinical efficacy of HDM-SCIT in patients with AR, and also correlated with improvement of the symptom scores. Consistently, grass pollen SLIT induces Lol p 1-specific memory B cells with upregulated expression of surface IgG4, CD23, and CD29 [ 123 ]. The serum C-X-C motif ligand 13(CXCL13) but not B cell-activating factor after HDM-SCIT in pediatric AR have clinical values for biomarkers, being CXCL13 level higher in effective AIT group [ 124 ].…”
Section: Predictive Biomarkers For Ait Outcomes In Allergic Diseasesmentioning
confidence: 93%
“…The transcriptional maturity of IgE + ASC in bone marrow 137,138 2017 IgG1 + B cells shown to hold IgE memory for recall responses in mice 43 2018 Transcriptome of human IgE plasmablasts published, confirming SHM 38 2019 General acceptance that IgE memory resides primarily among non-IgE mBC in humans 147,201 2019 Discovery of TFH13 cells and regulation of IgE affinity by IL-13 46 2021 Neuritin discovered to suppress IgE responses 49 2023 Type 2 memory B cells identified 44,45,144 although accurate determination of incidence is challenging and varies by geographic location, milk and egg allergies tend to predominate in infants, 57,61 although in countries with high consumption of fish, fish allergies can be quite prevalent in infants and children as well. 62 The majority of milk and egg allergies resolve by age 12.…”
Section: Box 1 Major Unknowns In Cellular Ige Response Biologymentioning
confidence: 99%
“…SCIT and SLIT have been proven to effectively reduce symptoms and medication use and modify disease pathology, leading to a long‐term curative effect after stopping treatment 66–68 . AIT relies on the modifying effect on innate and adaptive immune responses associated with type 2 inflammation 69,70 . The effects of AIT on innate responses include reducing the local infiltration of mast cells, basophils, and eosinophils; decreasing circulating frequencies of ILC2; elevating complement C1Q‐expressing regulatory DCs; and restoring epithelial cell integrity 71–73 .…”
Section: Treatment Strategies For Armentioning
confidence: 99%
“…[66][67][68] AIT relies on the modifying effect on innate and adaptive immune responses associated with type 2 inflammation. 69,70 The effects of AIT on innate responses include reducing the local infiltration of mast cells, basophils, and eosinophils; decreasing circulating frequencies of ILC2; elevating complement C1Q-expressing regulatory DCs; and restoring epithelial cell integrity. [71][72][73] Regarding adaptive immune responses, AIT modifies the responses of T and B cells specific to allergens and upregulates regulatory B (Breg) and T (Treg) cells, thereby downregulating allergic immune responses and causing a shift from allergen-specific IgE to allergen-specific IgG4.…”
Section: Aitmentioning
confidence: 99%